2020
DOI: 10.1369/0022155420911930
|View full text |Cite
|
Sign up to set email alerts
|

High-fat Diet Alters the Glycosylation Patterns of Duodenal Mucins in a Murine Model

Abstract: High-fat diet (HFD) alters the glycosylation patterns of intestinal mucins leading to several health problems. We studied by histochemical and lectin-binding methods mucin alterations in the duodenum of mice fed a HFD for 25 weeks. Histochemical methods included periodic acid–Schiff, alcian blue pH 2.5, and high-iron diamine. Lectin-binding experiments were performed with SBA, PNA, WGA, MAA-II, SNA, ConA, UEA-I, LTA, and AAA. SBA, PNA, WGA, MAA-II, and SNA were tested also after desulfation and ConA after peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…24 Previous studies have also shown that dietary fiber inclusion can induce changes in mucin glycosylation. [25][26][27] However, due to limitations of the techniques used, these studies could only distinguish changes in acidic, neutral, or fucosylated glycans and lacked detailed structural characterization of the gut mucin glycans.…”
Section: Introductionmentioning
confidence: 99%
“…24 Previous studies have also shown that dietary fiber inclusion can induce changes in mucin glycosylation. [25][26][27] However, due to limitations of the techniques used, these studies could only distinguish changes in acidic, neutral, or fucosylated glycans and lacked detailed structural characterization of the gut mucin glycans.…”
Section: Introductionmentioning
confidence: 99%
“…So, it can considerably weaken the response of proliferation of GCs that are caused by the stimulation of the fibers. HFD not only contains less fibers but also can effectively reduce glycosylated residuals in the GCs, 35 elevate the enteral and circulating bile acid levels, such as deoxycholic acid, which are cytotoxic, 36 thereby significantly decreasing the number of GCs. Thus, it is feasible that exercise may ameliorate these undesirable physiological and biochemical processes by balancing energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Western diets rich in saturated fats have been reported to cause a marked change in the functionality of the mucus barrier. In this context, reduction in fucosylated and sulfated residuals in the goblet cells of villi was observed in mice fed with a high fat diet during 25 weeks [67]. Another study revealed that a prolonged high fat diet leads to ER and oxidative stress in goblet cells reducing the production and secretion of mucins needed for a protective barrier [68].…”
Section: Dietary Modulationmentioning
confidence: 98%